Epitome und Erzählung: die Rekapitulationen am Ende der Odyssee - Grethlein, Jonas (Poetica, 2020)
The article interprets the two summaries at the end of the "Odyssey", namely Odysseus’ narration of his adventures in book 23 and Amphimedon’s account of the events on Ithaca in book 24, as embedded epitomes. The interpretation highlights the complexity of the "Odyssey’s" ending and explores the hermeneutic and temporal dimensions of epitomizing, which, it is suggested, are closely linked to cognitive processes.
Gesehen am 02.06.2021